Properties of solitary electric potential hump in electron plasma - Maslov, V.I.; Stomin, V.L. (Вопросы атомной науки и техники, 2000)
The properties of collective electric trap for electrons of charged beam are investigated theoretically. This electron beam propagates along magnetic field in cylindrical tube. It is shown that part of beam electrons are trapped in the system.